The efficacy of cetuximab in a tissue-engineered three-dimensional in vitro model of colorectal cancer. (17th July 2014) - Magdeldin, Tarig; López-Dávila, Víctor; Villemant, Cecile; Cameron, Grant; Drake, Rosemary; Cheema, Umber; Loizidou, Marilena
The preclinical development process of chemotherapeutic drugs is often carried out in two-dimensional monolayer cultures. However, a considerable amount of evidence demonstrates that two-dimensional cell culture does not accurately reflect the three-dimensional in vivo tumour microenvironment, specifically with regard to gene expression profiles, oxygen and nutrient gradients and pharmacokinetics. With this objective in mind, we have developed and established a physiologically relevant three-dimensional in vitro model of colorectal cancer based on the removal of interstitial fluid from collagen type I hydrogels. We employed the RAFT™ (Real Architecture For 3D Tissue) system for producing three-dimensional cultures to create a controlled reproducible, multiwell testing platform. Using the HT29 and HCT116 cell lines to model epidermal growth factor receptor expressing colorectal cancers, we characterized three-dimensional cell growth and morphology in addition to the anti-proliferative effects of the anti–epidermal growth factor receptor chemotherapeutic agent cetuximab in comparison to two-dimensional monolayer cultures. Cells proliferated well for 14 days in three-dimensional culture and formed well-defined cellular aggregates within the concentrated collagen matrix. Epidermal growth factor receptor expression levels revealed a twofold and threefold increase in three-dimensional cultures for both HT29 and HCT116 cells in comparison to two-dimensional monolayers, respectively ( p < 0.05; p < 0.01). Cetuximab efficacy was significantly lower in HT29 three-dimensional cultures in comparison to two-dimensional monolayers, whereas HCT116 cells in both two-dimension and three-dimension were non-responsive to treatment in agreement with their KRAS mutant status. In summary, these results confirm the use of a three-dimensional in vitro cancer model as a suitable drug-screening platform for in vitro pharmacological testing.